Respiração, voz e qualidade de vida na síndrome pós-Covid-19 - Souza, Juliana Alves (2024)
Post-COVID-19 Syndrome is characterized by the persistence of symptoms weeks or months after Coronavirus disease 2019 (COVID-19) and is prevalent in 44% to 63% of individuals admitted to the Intensive Care Unit (ICU). This prospective observational, cross-sectional, and longitudinal study aimed to verify and relate, at different time points, the lung function, voice, and quality of life of individuals with Post-COVID-19 Syndrome who were admitted to the ICU/COVID-19 of the Hospital from the Federal University of Santa Maria during the first and second waves of the disease and were referred to the Post-COVID-19 Rehabilitation Outpatient Clinic. The selected patients were evaluated 30 days after discharge and re-evaluated at two additional times, on average every four months. Anamnesis, audiological screening, and video laryngoscopy were carried out. Lung function was assessed by the degree of dyspnea, spirometry, manovacuometry, and distance covered in the six-minute walk test (6MWT); the voice by maximum phonation time (MPT), sound pressure level (SPL), auditory-perceptual vocal analysis, and the questionnaires Screening Index for Voice Disorder, Voice Handicap Index, and Voice-Related Quality of Life (V-RQoL); and quality of life by the 36-Item Short-Form Health Survey (SF-36). One hundred and twenty patients were referred for rehabilitation, of which 70 patients were included in the study of the accuracy of MPT to estimate lung function; 50 included in the study on the risk of dysphonia, vocal handicap, and laryngological findings; 48 were followed longitudinally, 45 returned for the first follow-up, and only 13 for the second. The results showed that 24% of patients had a reduction in forced vital capacity, with significantly reduced MPT values for the vowel /a/, fricative /s/, numerical counting time, and number reached. The cutoff points for lung involvement were 8.83, 7.50, and 8.80 seconds, respectively, and number 13 in the count, with an accuracy of 70%. The most reported vocal symptoms among the 50 patients were hoarseness, dry throat, throat clearing, and tiredness when speaking, with a significant risk of dysphonia and vocal handicap in women. The prevalent laryngeal findings were edema and erythema, with a significant association with orotracheal intubation. The follow-up results showed that, on average, eight months after hospitalization, there was a significant reduction in the degree of dyspnea; increased respiratory muscle strength; distance covered in the 6MWT; MPT for /a/; usual and minimum SPL; with better dyspnea and 6MWT scores correlated with increased MPT for /a/. However, women's MPT for /a/ was still reduced, and both sexes had mild and moderate persistent dysphonia. The SF-36 domains physical function, limitations due to physical and emotional health, and perception of general health status improved, as did the socio-emotional and total V-RQoL scores. However, in women, the physical V-RQoL score was still reduced. The findings of this study help to understand the impact of severe COVID-19 on lung function, voice, and quality of life and highlight dysphonia as a persistent symptom, especially among women, that should be further investigated. Therefore, it is suggested that rehabilitation for Post-COVID-19 Syndrome should be dynamic, continuous, and multidisciplinary.